A modulation optimization‐based active thermal control method for H‐bridge rectifiers. Issue 13 (6th August 2021) - Chen, Wenbo; Chen, Shujing; Qiu, Hongbo; Cheng, Hong
Abstract: As one of the most widely adopted topologies in power electronics, the H‐bridge circuit has been used for numerous kinds of power converters. With the emphasis on reliability and lifetime management of power converters, it could be helpful to decrease or rebalance the thermal stress of semiconductors to prolong the entire converter's lifetime. However, current switching frequency or power routing‐based methods will more or less deteriorate the performance of converters. Therefore, an active thermal control method for the H‐bridge rectifier is presented here, which has limited influence on the converter. This method puts four bridgeless modulation types into operation by the redundant switching states of the H‐bridge. The power losses were reduced by alternately changing a couple of bridgeless modes. Finally, the effectiveness of this active thermal control method has been analyzed of loss and temperature comparisons and validated with simulation and experimental results.